Analysis of Photo Sharing and Visual Social Relationships: Instagram as a case study. (2nd January 2017) - Serafinelli, Elisa
Abstract : This article discusses how visuality, through the mobility of Instagram, modifies individuals' mediated lives. In particular, it examines how Instagram transforms individuals' perceptions of their interpersonal relationships. It advances a critical re-reading of the concept of mobility (smart mobile devices) and the new approach to sociality. Conducting an empirical examination, this article delineates the changing dynamics that digitality determines within contemporary life experiences. Findings show that the ubiquitous use of smart mobile devices leads individuals towards the development of new forms and conceptions of mobile mediated visualities. In order to understand the rise of new visual practices based on Pink's ethnographic work, this article considers how relationships develop among individuals, visual technologies, practices and images, society and culture. A qualitative approach informed by netnography, computer-mediated interviews and visual analysis is employed in this study. The critical analysis of 44 participant interviews and their photo sharing behaviour presents the transformations that the mediation and mobility of Instagram bring into everyday relations between humans and technologies. The increased use of social media shows how sociality is affected and mediated by new mobile technologies. Although the social potentiality of (visual) social relationships itself does not offer a variety of verbal communication mechanisms, it encourages offline meetings or the relocation onto other social media. This shows that every alteration in the structure of societies has influence on individuals and on their means of expression.